Evaluasi manajemen majelis taklim menuju ketakwaan sempurna - Afiffudin; Tamam, Abas Mansur; Hafidhuddin, Didin (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
In the implementation of the taklim majelis in addition to the ideal criteria in the institution and organization of the taklim, a set of supporters is also needed as mandated in the Decree of the Director General of Islamic Guidance No. 802 of 2014 concerning “Standards for the Development of Mosque Management, Ministry of Religion of the Republic of Indonesia. Mosque Management Guidance includes three aspects, namely idara (management and management of mosques), imarah (mosque prosperity management) and riayah (maintenance and development of mosque facilities). Fundamentally, the three aspects of iarah, imarah and riayah apply to all mosque typologies both for state mosques, national mosques, grand mosques, grand mosques, large mosques, jami' mosques, historic mosques, public mosques in certain areas (public mosques) and also prayer rooms. Synthesis or combining the standard majelis taklim approach from the ministry of religion and also the basics of da'wah according to Islamic education is very important. The matrix format mentioned above is an initial form that needs to be further developed to evaluate the Ideal Mosque-Based Majelis Taklim. Some of the successes of the taklim majelis in terms of faith, piety, worship and morals are sometimes difficult to include in the matrix. While the progress of the majelis taklim can be measured by increasing the number of worshipers attending the majelis taklim, the number of worshipers praying five times fardlu, Eid al-Adha activities with the number of sacrificial animals, mosque activities such as TPA, PAUD, and Iqra Tahsin for children 7-12 years old. The more religious activities in the mosque, it can be concluded that the mosque-based majelis taklim is developing and progressing. Abstrak Dalam pelaksanaan majelis taklim selain kriteria ideal dalam kelembagaan dan penyelenggaraan taklim, juga diperlukan seperangkat pendukung seperti diamanahkan dalam Keputusan Dirjen Bimas Islam No. 802 tahun 2014 mengenai “Standar Pembinaan Manajemen Masjid, Kemenag Republik Indonesia. Pembinaan Manajemen Masjid meliputi tiga aspek yaitu idarah (pengelolaan dan kepengurusan masjid), imarah (pengelolaan kemakmuran masjid) dan riayah (pemeliharaan dan pengembangan fasilitas masjid). Secara mendasar ketiga aspek idarah, imarah dan riayah berlaku bagi semua typology masjid baik untuk masjid negara, masjid nasional, masjid raya, masjid agung, masjid besar, masjid jami’, masjid bersejarah, masjid umum di wilayah tertentu (masjid publik) dan juga mushala. Synthesa atau menggabungkan pendekatan standar majelis taklim dari kementerian agama dan juga dasar-dasar dakwah menurut pendidikan Islam sangatlah penting. Format matirk yang telah disebutkan di atas adalah bentuk awal yang perlu dikembangkan lebih lanjut untuk mengevaluasi Majelis Taklim Berbasis Masjid Yang Ideal. Beberapa keberhasilan majelis taklim dalam hal keimanan, ketakwaan, ibadah dan akhlak kadang-kadang sulit dimasukkan dalam matrik. Sementara kemajuan majelis taklim dapat diukur dengan peningkatan jumlah jamaah hadir dalam majelis taklim, jumlah jamaah shalat lima waktu fardhu, kegiatan Idul Adha dengan jumlah hewan kurban, kegiatan masjid seperti TPA, PAUD, dan Iqra Tahsin untuk anak 7-12 tahun. Semakin banyak kegiatan keagamaan dalam masjid maka dapat disimpulkan majelis taklim berbasis masjid tersebut berkembang dan mengalami kemajuan.